2018
DOI: 10.1016/j.biocon.2017.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Food for thought. Rainforest carrion-feeding butterflies are more sensitive indicators of disturbance history than fruit feeders

Abstract: Tropical forests have, and in many areas continue to experience both severe and subtle forms of human disturbance; most commonly from hunting, logging and clearance for agriculture. The ability to detect a full range of impacts is essential to understanding how biodiversity responds to human disturbance. Since monitoring the entire biodiversity of a tropical forest is an impossible task, specific groups of biodiversity are often used as biological indicators. Due to their relative ease in detection and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
0
15
0
1
Order By: Relevance
“…Butterflies play an important role in ecosystems as plant pollinators (Feber et al, 1997;Potts et al, 2016) and as prey for other organisms (Strong et al, 2000). Well-known to the general public, they are well monitored, recognised as indicators of environmental health (Whitworth et al, 2018) and as such they have been used to measure impact of factors such as climate change (Schweiger et al, 2012) and landscape fragmentation (Scriven et al, 2017). Comparatively, their ecology and abundance is much better known than any other invertebrate taxa (New, 1997).…”
Section: Butterflies As Models For Non-target Effects Of Pesticidesmentioning
confidence: 99%
“…Butterflies play an important role in ecosystems as plant pollinators (Feber et al, 1997;Potts et al, 2016) and as prey for other organisms (Strong et al, 2000). Well-known to the general public, they are well monitored, recognised as indicators of environmental health (Whitworth et al, 2018) and as such they have been used to measure impact of factors such as climate change (Schweiger et al, 2012) and landscape fragmentation (Scriven et al, 2017). Comparatively, their ecology and abundance is much better known than any other invertebrate taxa (New, 1997).…”
Section: Butterflies As Models For Non-target Effects Of Pesticidesmentioning
confidence: 99%
“…Short lifecycles and variability for their resilience capacities make insects good bio-indicators [5]. Many studies have demonstrated the advantages of Lepidoptera as bio-indicators in tropical [6][7][8][9] or temperate [10,11] ecosystems. For the Yucatan Peninsula, Pozo (2006) [12] endorsed nine butterfly species as environmental indicators of undisturbed tropical forest and seven for disturbed tropical forest.…”
Section: Introductionmentioning
confidence: 99%
“…disturbance on Lepidopteran biodiversity (see Table 1). However, in their comparison of carrion-and fruit-baited traps, Whitworth et al (2018) show that in addition to higher capture rates and attracting a wider array of the community, carrion-baited traps are more sensitive to rainforest disturbance effects and less susceptible to seasonal fluctuations. They therefore suggest that the community attracted to carrion-baited traps performs better as a biodiversity indicator group than the community associated with fruit-baited traps.…”
mentioning
confidence: 99%
“…A key part of this involves carefully selecting the most appropriate methods to target these groups. We should further question paradigms that exist for prevailing methods, as Whitworth et al (2018) and others have done (Barlow, Mestre, et al, 2007), and continue to explore how biodiversity within the upper reaches of the rainforest canopy might be differentially impacted to those close to the ground (Nakamura et al, 2017). If we utilize methodologies with precision that accurately assess habitat disturbance, we will enhance our ability to predict how forest ecosystems respond to human disturbances and recovery interventions at multiple scales.…”
mentioning
confidence: 99%
See 1 more Smart Citation